RANCANG BANGUN APLIKASI PENJUALAN BARANG KERAJINAN DAN MAKANAN BERBASIS ANDROID PADA DEWAN KERAJINAN NASIONAL DAERAH (DEKRANASDA) KOTA METRO - Dahlia, Tiara; Apsiswanto, Untoro (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Technological developments in the world are increasing rapidly, such as one in Indonesia, this forces entrepreneurs to be able to market their products online. At this time smartphones are widely used by the internet user community. With an increasingly modern era, there are many ways to sell a product or service, one of which is an online sales system where the product is offered via the internet or an application that can be reached using a smartphone device. Online sales are media for selling or offering a product via the internet. Customers can search, check prices, and whether or not products are available at the store before buying. In Metro City there are many MSMEs that make handicraft products such as bags, shoes, cloth, etc., there are also those that make various kinds of food which are usually used as souvenirs, therefore the Metro City Regional National Crafts Council (Dekranasda) cooperates with the City Government Metro has created a forum for MSMEs to deposit their products so they can be more easily sold and reached by all levels of society. The purpose of this research is to help market and sell products at Dekranasda Kota Metro and help Dekranasda Kota Metro provide sales services to consumers using an android-based application which is expected with this sales system more people can easily buy products as well as food souvenirs available at Dekranasda Kota Metro. The process of developing the system scheme used is OOSE (Object Oriented Software Engineering) from Jacobson with the initial technical stages, by building the boundaries of a system and then defining it by implementing and compiling its functions. Data analysis is describing the character or integrity according to use case. This method is a foundation for a design. model design, namely presenting data analysis and then turning it into a practical stage. model implementation, is a system that contains program code that has been set in the design model, model testing, is testing the entire build system whether it functions properly or not.